Process for recovering Li, Ni and Co
Patent Information
- Application Number
- JP2024548445
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2023-02-15
- Publication Date
- 2025-03-13
AI Technical Summary
【0013】 一般的な硫化剤は、Na2S、NaHS及びH2Sである。本発明では、硫化剤は、金属硫化物を形成するための沈殿剤として作用するのみならず、有利には、Me3+又はMe4+等の酸化状態のより高い原子価の金属の還元剤としても作用する。これは、以下で更に詳述される。
Smart Images

Figure 2025506687000001 
Figure 2025506687000002 
Figure 2025506687000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recovering Li, Ni and / or Co from solid starting materials, such as those including rechargeable lithium-ion batteries or scrap thereof. [Background technology]
[0002] Currently popular rechargeable battery chemistries involve cathode powders containing the metals lithium, nickel, manganese and cobalt (NMC). Other often used chemistries use cathode powders containing lithium, nickel, cobalt and aluminum (NCA) or lithium, nickel, cobalt, manganese and aluminum (NMCA). Possible future chemistries may replace lithium with sodium. When recycling any of these, separation of Ni or Co from alkali metals such as Li and Na is difficult.
[0003] There is an increasing need for recycling lithium-ion batteries, including both production waste and end-of-life batteries. This results in a complex waste stream in which all kinds of lithium batteries and their components, such as electrode foils, electrolytes, separators, casing materials, electrical or electronic components, may be further mixed with non-lithium batteries, such as nickel-cadmium, nickel-metal hydride and zinc-based batteries. These production waste and end-of-life battery derivatives are also available for recycling in the form of powder fractions or black agglomerates, which are the result of mechanical and / or thermal pretreatment.
[0004] The chemical complexity of the scrapped materials increases towards the end of the manufacturing process as more and more components are added to the product. Thus, battery cells and modules may contain a huge number of different elements, e.g., Al, Fe, Cu, Ni, Cr together with Ni, Co, Mn, Li, Na, Fe, Al, V, P, F, C, Ti and Mg in the cathode, Li, Ti, Si, C, Al and Cu in the anode, Li, F, P and volatile organic compounds in the electrolyte, and plastics with Cl, Br and Sb in the casing.
[0005] Due primarily to the increasing electrification of the automotive industry, the volume of used batteries is expected to exceed 100,000 tonnes per year over the next decade, and battery recycling business will grow accordingly.
[0006] US Patent Publication No. 2019152797 shows an example of a conventional battery scrap recycling process in which Co and Ni are extracted from the purified leach solution using solvent extraction. In this operation, a base such as NaOH or NH4OH is consumed stoichiometrically with the amount of Ni and Co recovered. The consumption of the base is a significant operational cost and also results in significant salt discharge, which can be problematic for the environment. Furthermore, the recovery of lithium from the waste solution is not straightforward due to the low Li concentration. The extraction steps are expensive because they usually require the use of specific, costly extractants and are carried out in multiple process steps.
[0007] Some battery recycling methods use a sulfiding agent to separate Ni and Co from elements such as Al, Li, F or Na. In CN102492858, a sulfide-based battery recycling method is proposed, which includes the steps of (1) leaching battery scraps, (2) removing Al and Fe by hydrolysis, and (3) precipitating Ni and Co sulfides from the solution using a sulfiding agent. Ammonium sulfide (NH4)2S is preferred as the sulfiding agent because it does not affect the pH of the solution. Although it avoids the use of solvent extraction and its drawbacks, this recycling approach has the same drawbacks as the traditional approach: (1) it consumes base stoichiometrically with the amount of Ni and Co precipitated, and (2) the recovery of lithium from the waste solution is not straightforward.
[0008] Several battery recycling methods have been proposed that do not consume base and directly convert Ni or Co oxides to sulfides. In CN111994966, battery scrap is roasted with hydrogen sulfide at high temperatures of 600-1000°C. In US2021277531, gaseous sulfur is used to sulfurize Ni and Co in battery scrap at 1000°C. This method allows for the separation of Ni and Co from Al, Li and Mn by flotation. However, the use of gaseous sulfur or hydrogen sulfide at high temperatures makes this method industrially difficult due to corrosion, complex flue gas treatment, and general safety issues. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] U.S. Patent Application Publication No. 2019152797 [Patent Document 2] China Patent Application Publication No. 102492858 [Patent Document 3] China Patent Application Publication No. 111994966 [Patent Document 4] US Patent Application Publication No. 2021277531 [Non-patent literature]
[0010] [Non-Patent Document 1] Monhemius(Monhemius J.; 1977; Precipitation diagrams for metal hydroxides, sulfides, arsenates and phosphates) Summary of the Invention
[0011] It is therefore an object of the present invention to provide a low temperature, selective method for the separation of Li from Ni and / or Co containing solids using a sulfiding agent while reducing the consumption of base. [Means for solving the problem]
[0012] The present invention advantageously uses the difference in the solubility of certain metal sulfides. Monhemius (Monhemius J.; 1977; Precipitation diagrams for metal hydroxides, sulfides, arsenates and phosphates) shows that the theoretical solubility of metal sulfides is Cu. 2+ <Co 2+ <Ni 2+ <Mn 2+ <Li + Metal sulfide precipitation is often used in wastewater treatment.
[0013] Common sulfurizing agents are Na2S, NaHS and H2S. In the present invention, the sulfurizing agent not only acts as a precipitant to form metal sulfides, but also advantageously acts as a precipitant to form metal sulfides, such as Me 3+ Or Me 4+ It also acts as a reducing agent for higher valent metals in the oxidation state, such as ZnO, Fe, FeCl, etc. This is discussed in more detail below.
[0014] In known methods, sulfide precipitation with H2S is typically carried out starting from a Ni-containing solution. Such a solution may already be acidic, especially if it originates from a leaching operation. The sulfide precipitation further generates more acid according to the reaction: NiSO4 + H2S → NiS + H2SO4
[0015] Thus, precipitation of Ni with H2S generates an equimolar amount of additional acid, which needs to be neutralized: if it is not neutralized, the equilibrium of the precipitation reaction will shift to the left and the precipitation reaction will slow down, not go to completion, or even stop altogether.
[0016] Neutralization involves the addition of a base, which necessarily results in a salty solution.
[0017] In contrast to the above, the present method starts from solid Ni oxides and converts them directly into sulfides in a wet process as follows: NiO+H2S→NiS+H2O
[0018] No additional acid is formed, therefore no neutralizing base is required and the formation of additional salts is avoided entirely.
[0019] The metals occur mainly as oxides in battery scrap. Ni and Co are 2+ As and / or Me 3+ In the latter case, reduction to the divalent state occurs along with conversion to a sulfide. A typical example is the conversion of CoO sesquioxide to CoS as follows: Co2O3+3H2S→2CoS+3H2O+S
[0020] In this reaction, Co oxide is reduced and converted to Co sulfide, while H2S is oxidized to elemental S. As Ni and Co oxides are converted to sulfides, lithium or manganese oxides are liberated from the matrix. When converting a typical mixed oxide, corresponding to the so-called 3:1:1 Ni:Co:Mn battery chemistry, additional acid is required to dissolve the Li and Mn. This is represented by the equation: 10LiNi 0.6 Co 0.2 Mn 0.2 O2+13H2S+7H2SO4→5Li2SO4+2MnSO4+2CoS+6NiS+5S+20H2O As shown by:
[0021] In contrast to known methods in which a neutralizing base is required, the present method allows the pH to be controlled by the addition of an acid. No complementary salts are produced. Preferably, the acid is a mineral acid such as H2SO4.
[0022] A solution containing Li and other soluble metals is obtained by the described method. To recover Li from this solution, several options are available. For example, Li can be precipitated as an insoluble Li salt, such as Li2CO3. To precipitate pure Li salts, it is preferable to first remove other metals, such as Al or Mn, from the Li solution. Other methods, such as solvent extraction or crystallization methods, can also be employed to process the Li-containing solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] A first embodiment includes a method for separating Li from oxides of one or more of Co and Ni contained in a feed, comprising the steps of: - contacting the feed in an aqueous medium with a sufficient amount of sulfiding agent to convert most of the Co and / or Ni to sulfides, and a sufficient amount of mineral acid to reach a pH of 1-3, at an absolute pressure of less than 0.3 MPa, thereby forming an aqueous slurry containing solid Co and / or Ni sulfides, and a solution containing most of the Li; - separating the solid from the solution, thereby obtaining a solid containing Co and / or Ni and a solution containing most of the Li. A method is described, including:
[0024] Besides oxides of Li, and Co and / or Ni, a typical battery scrap based feed may also contain anode materials such as carbon, electrode foil and electrolyte.
[0025] Preferably, at least the majority of the Co and / or Ni contained in the feed is in the form of their respective metal oxides, more preferably at least 80% by weight, most preferably at least 90% by weight. The remainder may comprise Co and / or Ni in metallic form.
[0026] A "major portion" of an element or compound means at least 50% by weight of that element or compound relative to its total process input.
[0027] The mineral acid is preferably selected from the list consisting of H2SO4, HCl, H3PO4 and HNO3, or mixtures thereof. H2SO4 and HCl are more preferred.
[0028] The contacting step is advantageously carried out in a reactor, preferably a closed reactor, to avoid the release of harmful gases.
[0029] By aqueous medium is meant a water-based solution. The aqueous medium facilitates the handling of the contents of the reactor, such as mixing or pumping. The aqueous medium may already contain some of the other components involved in the reaction or these may be added later. It may contain, in particular, a mineral acid.
[0030] The sulfurizing agent used in the contacting step should obviously be one that is reactive with the Co and / or Ni oxides. Suitable sulfurizing agents should therefore preferably be at least partially soluble in aqueous media. Otherwise they cannot function efficiently as a source of sulfide for the described process.
[0031] The pH ranges listed correspond to the pH of the solution measured at 40° C. after purging of any dissolved H2S. By operating at the higher end of the claimed pH range, e.g., between 3.5 and 5, the overall yield of conversion of Co and / or Ni to sulfides is reduced. Therefore, contact with a sufficient amount of mineral acid to reach a pH of 1.5 to 3.3 is preferred, with a pH of 2 to 3 being more preferred.
[0032] In battery scrap, Li is most likely present as Li2O, LiF, LiPF6, Li2CO3 or LiOH. Acid must be added stoichiometrically to dissolve all the contained Li compounds.
[0033] By working in the indicated pH range, it is possible to maximize the dissolution of lithium, while simultaneously promoting the formation of Ni and / or Co sulfides. In this way, soluble compounds such as Li are efficiently separated from the solid Ni and / or Co sulfides. If too much acid is added, Ni and Co oxides may partially dissolve. Therefore, the addition and consumption of acid during the process should be well controlled by monitoring the pH and reaching a pH within the limits defined above. This means that such a pH should be reached at the end of a batch process or that this pH should be maintained if the process is carried out as a continuous process.
[0034] In a further embodiment, the sulfiding agent used in the contacting step is one or more of H2S, NaHS and Li2S. H2S and NaHS are the preferred sources of sulfide. H2S is more preferred. It may be added as is, but in industrial setups it can also be generated from H2, S or metal sulfides. Using a suitably equipped reactor, H2S can be introduced by injection into the slurry or by working under an H2S atmosphere. Preferably, this H2S atmosphere is generated in the head space of the reactor. For safety reasons, working below atmospheric pressure is advantageous. On the other hand, working with higher pressures of H2S accelerates the reaction rate. The amount of sulfiding agent added is preferably sufficient to saturate the slurry with H2S. Saturation is easily confirmed by monitoring the rate of absorption of H2S by the reaction mixture. Saturation results in the optimal rate.
[0035] NaHS is assumed to form H2S, which dissolves and reacts with the slurry, and NaOH, which reacts with the acid to form a salt. This salt is produced in limited quantities, but is less desirable. Na2S can also be used as a sulfiding agent. However, this produces twice as much salt as NaHS, and is therefore even less desirable. Ammonium sulfide can also be used.
[0036] A suitable sulfurizing agent should preferably be at least partially soluble in the aqueous medium. For example, Li2S reacts with the slurry to form a soluble Li salt and a soluble sulfide. On the other hand, sulfides that are insoluble under the described conditions, such as CuS, are not considered to be suitable sources of sulfide or sulfurizing agents according to the present invention.
[0037] In a further embodiment, the sulfiding agent used in the contacting step is generated in situ by adding elemental sulfur under reducing conditions, for example, elemental S can be reduced in the reactor using H, thereby forming HS.
[0038] In a further embodiment, the amount of mineral acid in the contacting step is generated at least partially in situ by adding a solution containing dissolved Co and / or Ni.
[0039] Usually, the mineral acid is added as is. However, the acid can also be generated by adding a solution containing, for example, NiSO4 or NiCl2. Upon contact with the sulfiding agent, these metals precipitate and generate the acid in situ. A further advantage of this embodiment is the increase in the total amount of Co and / or Ni in the process. The process is robust enough to handle Co and / or Ni containing solutions from impure waste streams.
[0040] In a further embodiment, the contacting step is carried out in a continuous operation. In such a configuration, the feed and acid are added continuously to the reactor while the slurry is extracted from the reactor. The addition and extraction can also be carried out batchwise, for example repeatedly, every 30 minutes. Continuous operation has several advantages. First, continuous operation enhances the use of the reactor equipment. Second, the quality of the solid Co sulfide and / or solid Ni sulfide is more constant since they are formed in a steady state regime. This facilitates further refining.
[0041] In a further embodiment, the solid obtained in the separation step comprises at least 70% Co and / or Ni, preferably at least 85% Co and / or Ni, more preferably at least 90% Co and / or Ni.
[0042] This method allows high recovery of valuable metals such as Co and / or Ni, which are important in industrial construction.
[0043] In a further embodiment, the solution obtained in the separation step comprises at least 70% Li, preferably at least 85% Li, more preferably at least 90% Li.
[0044] Separation of Li and other impurities from the solid Co and / or Ni sulfides facilitates further purification of these sulfides.
[0045] Mn is present in most cathode active materials and therefore ends up in battery scrap as well. Therefore, in a further embodiment, the feed further contains an oxide of Mn. The Mn is dissolved together with the lithium, thereby obtaining a solution containing most of the lithium and most of the manganese.
[0046] In a further embodiment, the solution comprises at least 70% Mn, preferably at least 85% Mn, more preferably at least 90% Mn.
[0047] According to this method, Mn is dissolved. No Mn sulfides are produced and therefore Mn does not report to the residue. This is a further significant benefit of this method since it facilitates the refining of the solid residue containing Co and / or Ni sulfides.
[0048] Besides Li and Mn, the method advantageously also dissolves a number of further impurities that may be present in battery scrap, such as Al, F, W, Si, Ca, Mg, P, C, K, Fe, Cl, SO4 and Na. Other impurities such as Cu, Zn, Pb and Cd report to the solid residue.
[0049] Dissolution of Mn and other soluble impurities also consumes stoichiometric amounts of acid.
[0050] In a further embodiment, the metal oxide contained in the feed is at least in the form of a powder, preferably having an average particle size D50 (volume median) of less than 100 μm, more preferably less than 50 μm, and most preferably less than 30 μm.
[0051] The particle size distribution is measured according to the ASTM B822-97 standard.
[0052] Metal oxides are more likely to react when present in the form of powder. Therefore, in industrial configurations, average particle sizes of less than 100 μm, less than 50 μm, or even less than 30 μm are preferred. Such powders do not need to be dry powders, which can also come from wet processes, such as filter cakes. This is particularly advantageous, since the formation of Ni and Co sulfides has been found to be the rate-limiting step.
[0053] In a further embodiment, the mixed oxide is derived from Li-ion batteries, battery scrap and / or their production waste. Of greatest economic interest in this respect are all the components and materials from the cathode material used in these Li-ion batteries.
[0054] In a further embodiment, the method is carried out at a temperature of 80° C. or less, preferably 65° C. or less, more preferably 50° C. or less. The method may be carried out at a wide temperature range from 15° C. up to the boiling point of the aqueous solution. Even at moderate temperatures, such as 65° C. or less, sufficient reaction rates have been observed. At lower temperatures, H2S absorption in the reaction mixture increases and corrosion is limited. Thus, temperatures of 65° C. or less are preferred.
[0055] The reaction is slightly exothermic and spontaneously heats the aqueous slurry to a temperature of 40-50°C. Therefore, advantageously, no external heating is required. The process will also work at temperatures below 40°C, but this is not practical as active cooling would be required. Therefore, it is most preferred to operate in the range of 40-50°C without additional heating or cooling.
[0056] In a further embodiment, the amount of mineral acid is predetermined according to a stoichiometric reaction and the addition is carried out in at least two steps, the first addition step being limited to a maximum of 80%, preferably a maximum of 90%, of the predetermined amount.
[0057] The proposed control approach minimizes the need for on-line measurement equipment, thus reducing the impact of measurement deviations and increasing the robustness of the process. Furthermore, by adopting this approach, the rate of the process is determined by the formation of sulfides and not by the availability of H2SO4 or other mineral acid. By adopting this approach and keeping the mineral acid added substoichiometric in the first addition step, time is usually saved.
[0058] In a further embodiment, the first addition step is completed at a pH above 3.3. The second or subsequent addition steps are completed at a pH between 1.5 and 3.
[0059] A multi-step process is advantageous in which most of the process is carried out at a moderate to high pH, such as above 3.3, and in the second or subsequent addition steps the pH is lowered to between 1.5 and 3. The rate of sulfide formation is higher at higher pH. For this reason, it is advantageous to carry out most of the process at a relatively high pH, since sulfide formation becomes the rate-limiting step. The lower pH in the second or subsequent addition steps is selected to maximize the dissolution of Li, Mn and other impurities. Optionally, a solid-liquid separation may be carried out after each such addition step. Most of the conversion to sulfides is usually carried out in the first reaction step, and then completed in the second or subsequent addition steps. Since sulfide formation does not occur at a pH below 1, the process needs to be completed at a pH between 1 and 5. By operating at a pH above the upper limit, the dissolution of Li and Mn may be insufficient.
[0060] After completion of the process, the pH can be further lowered to below 1.5 to maximize the removal of impurities. Indeed, the metal sulfides formed will not redissolve without an oxidizing agent, although some impurities may be eliminated from the residue.
[0061] The solid residue obtained in the separation step of the solid from the solution, containing a majority of the Co and / or Ni as Co and / or Ni sulfides, can be further processed in various ways. Hydrometallurgical processing of the solid residue is the preferred option.
[0062] Thus, in a further embodiment, a method is described in which the solid residue is used as a starting material in a subsequent hydrometallurgical refining process. - leaching the solid residue containing Co and / or Ni sulphides with a mineral acid, preferably H2SO4, thereby obtaining a Ni- and / or Co-containing solution; - separating the solution from the insoluble solids under conditions such that the solids remain; - crystallizing Ni and / or Co from a Ni and / or Co-containing solution, preferably as Ni and / or Co sulfate; Includes.
[0063] The production of a solid residue containing Mn-depleted Co and / or Ni sulfides has several advantages for hydrometallurgical refining processes: it allows for a more robust process since the Mn does not dilute the Ni and / or Co-containing solution, avoiding the need to separate the Mn by solvent extraction or the like.
[0064] The sulfide leaching can be carried out at very high acidity to promote the formation of H2S and recycle the H2S formed during leaching to the conversion process, thereby limiting the consumption of H2S in the conversion process and limiting the consumption of oxidant in the leaching process.
[0065] The solid residue containing Co and / or Ni sulfides may also contain some C from the anode and metal impurities such as Al and Cu from the current collector sheets. Therefore, prior to sulfide leaching, a solid-solid separation can be performed to separate the Co and / or Ni sulfides from the C and / or metal impurities. Flotation may be a suitable method.
[0066] The process for obtaining Co and / or Ni sulfides efficiently removes not only Li but also other impurities. As a result, subsequent hydrometallurgical refining processes benefit from higher purity and also higher quality, for example when crystallizing Ni and / or Co.
[0067] Subsequent pyrometallurgical processing of the solid residues containing Co and / or Ni sulfides is another option. Methods similar to matte smelting are suitable. Matte smelting converts the solid residues into sulfide alloys and oxide slags. In such high-temperature processing of the solid residues, temperatures above 1000°C, preferably above 1200°C, or even above 1400°C in cases where the compounds are more difficult to smelt, are used, the temperatures being chosen to ensure liquid alloys and slags. The abovementioned C and Al in the solid residues contribute to the heat generation for such methods.
[0068] Therefore, in a further embodiment, a method is described in which the solid residue is used as starting material in a subsequent pyrometallurgical refining process.
[0069] Many conventional Ni-Co smelters are designed to process sulfide materials such as Ni or Cu matte, and therefore are equipped to further process the sulfided Co and / or Ni in the solid residue into pure Ni and / or Co products.
[0070] Optionally, the residue containing Co and / or Ni sulfides is subjected to an additional leaching step. An aqueous mineral acid solution with a pH between 0.5 and 2 can be used to further dissolve the Li remaining in the residue. As it may also dissolve small amounts of Co and / or Ni, the solution from this leaching step can advantageously be recycled to the contacting step, where it serves as a source of part of the aforementioned aqueous medium and mineral acid.
[0071] The present invention is further illustrated in the following examples. EXAMPLES
[0072] (Example 1: Using H2S at 60°C on pyrolyzed black mass) 250 g of black agglomerate is added to a beaker. 0.8 L of water is added and the mixture is stirred. The black agglomerate comes from an end-of-life battery and was pyrolyzed at 550° C. for 3 hours under N2 atmosphere to liberate the cathode powder from the alumina foil. The black agglomerate is obtained after crushing and sieving. The black agglomerate contains 12% Ni, 7.2% Mn, 3.3% Co, 3.1% Li, 3.8% Al, 1.5% Cu and 1.8% F. The remainder of the agglomerate contains mainly C, P and O.
[0073] H2S is injected into the slurry at a constant rate of 10 g / h. The temperature is adjusted to 60°C. H2SO4 solution (1000 g / L) is added at a constant rate of 15 g / h. During the experiment, the temperature is maintained at 60°C, the pressure in the reactor is maintained at 0.95 bar, and H2S is continuously injected at the specified rate. Samples of the slurry are taken every hour. The samples are cooled to 40°C, purged with N2 for 30 minutes, and then the pH is measured. After about 15 hours, when the pH of the slurry reaches 2.1, the addition of H2SO4 is stopped.
[0074] The slurry is filtered through a Buchner filter to yield a solution and a solid residue. 156 g of dry solid residue and 0.9 L of solution are obtained.
[0075] The mass balance of the complete experiment can be seen in Table 1 below.
[0076] [Table 1]
[0077] This experiment shows that under the current process conditions, over 95% of the Li and Mn dissolves, while over 90% of the Ni and Co remains in the solid residue, minimizing dissolution of Ni and Co.
[0078] Example 2: Using H2S at 40°C on pyrolyzed black mass 300 g of black agglomerate is added to a beaker. 0.8 L of water is added and the mixture is stirred. The black agglomerate comes from an end-of-life battery and was pyrolyzed at 550° C. for 3 hours under N2 atmosphere to liberate the cathode powder from the alumina foil. The black agglomerate is obtained after crushing and sieving. The black agglomerate contains 20% Ni, 12.4% Mn, 10.5% Co, 4.55% Li, 5.2% Al, 6.1% Cu and 2.6% F. The remainder of the agglomerate contains mainly C, P and O.
[0079] H2S is injected into the slurry at a constant rate of 10 g / h. The temperature is adjusted to 40°C. H2SO4 solution (1000 g / L) is added at a constant rate of 24 g / h over a period of 15 hours. During this period, the temperature is maintained at 40°C and H2S is continuously injected at the specified rate. After this period, the pH of the slurry is 2.8.
[0080] The slurry is filtered through a Buchner filter resulting in a solution and a solid residue. 194 g of dry solid residue and 0.95 L of solution are obtained. The mass balance of the complete experiment can be seen in Table 2 below.
[0081] [Table 2]
[0082] This experiment demonstrates that the yield obtained at 40°C is similar to that obtained in Example 1 at 60°C.
[0083] Example 3: Using NaHS and H2SO4 at 80°C in a mechanical black block 300 g of black lump are added to a beaker. 0.8 L of water is added and the mixture is stirred. Mechanical black lump is battery production scrap obtained after crushing ("wet crushing") and sieving. The black lump contains 18% Ni, 6.5% Mn, 6.5% Co, 3.8% Li, 1.5% Al, 0.4% Cu and 0.8% F. The remainder of the lump contains mainly C and O.
[0084] NaHS solution (300 g / L) is injected into the slurry at a constant rate of 115 g / h. The temperature is adjusted to 80° C. H2SO4 solution (1000 g / L) is added at a constant rate of 45 g / h over a period of 7 hours. During this period, the temperature is maintained at 80° C. and NaHS is continuously injected at the specified rate. After this period, the pH of the slurry is 3.
[0085] The slurry is filtered through a Buchner filter resulting in a solution and a solid residue. 302 g of dry solid residue and 1.4 L of solution are obtained. The mass balance of the complete experiment can be seen in Table 3 below.
[0086] [Table 3]
[0087] This experiment demonstrates that NaHS can be used as a sulfiding agent instead of H2S.
[0088] Example 4: Using H2S and HCl at 60°C in a mechanical black block 250 g of black lump are added to a beaker. 0.8 L of water is added and the mixture is stirred. The black lump is battery production scrap and is obtained after crushing and sieving. The black lump contains 18% Ni, 6.5% Mn, 6.5% Co, 3.8% Li, 1.5% Al, 0.4% Cu and 0.8% F. The remainder of the lump contains mainly C and O.
[0089] H2S is injected into the slurry at a constant rate of 15 g / h. The temperature is adjusted to 60°C. HCl solution (430 g / L) is added at a constant rate of 14.3 g / h over a period of 15 hours. During this period, the temperature is maintained at 60°C and H2S is continuously injected at the specified rate. After this period, the pH of the slurry is 2.2.
[0090] The slurry is filtered through a Buchner filter resulting in a solution and a solid residue. 227 g of dry solid residue and 0.95 L of solution are obtained. The mass balance of the complete experiment can be seen in Table 4 below.
[0091] [Table 4]
[0092] This experiment demonstrates that HCl can be used as the mineral acid instead of H2SO4.
[0093] Example 5: Using H2S and H2SO4 at 60°C in a mechanical black block 116 g of H2SO4 solution (1000 g / L) and 0.95 L of water are added to the reactor. H2S is injected into the solution at a constant rate of 15 g / h. The temperature is adjusted to 60°C. The black agglomerates are added to the reactor at a constant mass flow rate of 12.5 g / h for 12 hours. The black agglomerates are end-of-life battery scraps and are obtained after crushing and sieving. The black agglomerates contain 23% Ni, 6.4% Mn, 6.5% Co, 4% Li, 1.8% Al, 2.1% Cu and 1.1% F. The remainder of the agglomerates mainly contain C, P and O.
[0094] The temperature is maintained at 60°C and H2S is injected continuously for 12 hours while the black mass is added. After the last amount of black mass is added, H2S is added at the specified rate for an additional 2 hours. After this period, the pH of the slurry is 2.2.
[0095] The slurry is filtered through a Buchner filter resulting in a solution and a solid residue. 167 g of dry solid residue and 1.2 L of solution are obtained. The mass balance of the complete experiment can be seen in Table 5 below.
[0096] [Table 5]
[0097] This experiment demonstrates that the order of addition does not significantly affect the dissolution yields of Li and Mn or the overall outcome of the experiment.
[0098] Example 6 (Comparative): Using H2S and H2SO4 at 60°C on pyrolyzed black mass The experimental conditions and input feed are the same as in Example 1, with only the amount of sulfuric acid added being different: a total of 110 g of H2SO4 solution (1000 g / L) is added to the slurry to reach a pH of 4.4 (compared to pH 2.1 in Example 1).
[0099] The slurry is filtered through a Buchner filter resulting in a solution and a solid residue. 153 g of dry solid residue and 0.86 L of solution are obtained. The mass balance for the complete experiment can be seen in Table 6 below.
[0100] [Table 6]
[0101] Working at a pH of 4.4 leads to dissolution of 80% Mn and 90% Li, which is lower than in Example 1 where Mn and Li are more than 95% dissolved.
Claims
1. 1. A method for separating Li from oxides of one or more of Co and Ni contained in a feed, comprising the steps of: contacting the feed in an aqueous medium with a sufficient amount of sulfiding agent to convert a majority of the Co and / or Ni to sulfides, and a sufficient amount of mineral acid to reach a pH of 1-3, at an absolute pressure of less than 0.3 MPa, thereby forming an aqueous slurry containing solid sulfided Co and / or solid sulfided Ni, and a solution containing Li; separating said solids from said solution, thereby obtaining a solid containing Co and / or Ni sulfides, and a solution containing most of the Li; A method comprising:
2. The sulfurizing agent used in the contact step is H 2 S, NaHS and Li 2 The method of claim 1 , wherein the first and second inputs are one or more of S.
3. 10. The method of claim 1, wherein the sulfiding agent used in the contacting step is generated in situ by adding elemental sulfur under reducing conditions.
4. 4. The method of claim 1, wherein in the contacting step, the amount of mineral acid is generated at least partially in situ by adding a solution containing dissolved Co and / or Ni.
5. 5. The process of claim 1, wherein the contacting step is carried out in a continuous operation.
6. 6. The method according to any one of claims 1 to 5, wherein the solid obtained in the separation step comprises at least 70% Co and / or Ni, preferably at least 85% Co and / or Ni, more preferably at least 90% Co and / or Ni.
7. 7. The method according to any one of claims 1 to 6, wherein the solution obtained in the separation step contains at least 70% Li, preferably at least 85% Li, more preferably at least 90% Li.
8. 8. The method of any one of claims 1 to 7, wherein the feed further contains oxides of Mn, and Mn is dissolved together with lithium, thereby obtaining a solution containing most of the lithium and most of the manganese.
9. 9. The method of claim 8, wherein the solution comprises at least 70% Mn, preferably at least 85% Mn, more preferably at least 90% Mn.
10. 10. The method according to any one of claims 1 to 9, wherein the metal oxide contained in the feed is at least in the form of a powder, preferably having an average particle size D50 of less than 100 μm, more preferably less than 50 μm, most preferably less than 30 μm.
11. 11. The method according to any one of claims 1 to 10, wherein the feed is derived from Li-ion batteries, battery scrap and / or their production waste.
12. 12. The process according to any one of claims 1 to 11, carried out at a temperature of 80°C or less, preferably 65°C or less, more preferably 50°C or less.
13. 13. The method according to any one of claims 1 to 12, wherein the amount of mineral acid is predetermined according to a stoichiometric reaction and the addition is carried out in at least two steps, the first addition step being limited to a maximum of 80%, preferably a maximum of 90% of the predetermined amount.
14. 14. The method of claim 13, wherein the first addition step is terminated at a pH above 3.3 and the second or subsequent addition step is terminated at a pH between 1.5 and 3.
15. 15. The method according to any one of claims 1 to 14, wherein the Co and / or Ni sulfides obtained in the solid separation step are used as starting material in a subsequent hydrometallurgical refining step.
Citation Information
Patent Citations
Method for separating enriched nickel and cobalt from battery waste leaching solution
CN102492858A
Method for manufacturing hydrogen sulfide atmosphere and recycling waste ternary positive electrode under high-temperature condition
CN111994966A
Method for preparing nickel / manganese / lithium / cobalt sulfate and tricobalt tetraoxide from battery wastes
US20190152797A1
Selective sulfidation and desulfidation
US20210277531A1